2006
DOI: 10.1093/eurheartj/ehi818
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative, randomized study evaluating three methods of mesenchymal stem cell delivery following myocardial infarction

Abstract: IC and EC injection of MSCs post-MI resulted in increased engraftment within infarcted tissue when compared with IV infusion, and IC was more efficient than EC. However, IC delivery was also associated with a higher incidence of decreased coronary blood flow. EC delivery into acutely infarcted myocardial tissue was safe and well tolerated and was associated with decreased remote organ engraftment with compared with IC and IV deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
433
3
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 560 publications
(454 citation statements)
references
References 30 publications
10
433
3
8
Order By: Relevance
“…Intracoronary infusion of MSCs may cause distal embolization and consequent no-reflow phenomena. Freyman et al 29 reported that intracoronary MSC infusion impaired coronary flow distal to the infusion site in half of their treated pigs. Similar to this report, the intracoronary administration showed elevated cardiac enzymes and micro infarctions in dogs with normal coronary arteries.…”
Section: Discussionmentioning
confidence: 98%
“…Intracoronary infusion of MSCs may cause distal embolization and consequent no-reflow phenomena. Freyman et al 29 reported that intracoronary MSC infusion impaired coronary flow distal to the infusion site in half of their treated pigs. Similar to this report, the intracoronary administration showed elevated cardiac enzymes and micro infarctions in dogs with normal coronary arteries.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, despite its potential benefits, cell transplantation is limited in its clinical applications. It has been established that only ∼5% of mesenchymal stem cells, which are one of the best candidates for cell therapy in heart diseases, can survive for 14 days in the infarcted porcine heart [164]. In addition, the survival rate of transplanted human mesenchymal stem cells in a mouse heart reaches <0.5% at 4 days after transplantation [165].…”
Section: Cell-based Therapies and Anoikismentioning
confidence: 99%
“…Using smooth muscle cells Yasuda et al reported viable graft cell counts of 15% at 1 week and 9% at 4 weeks after permanent LAD ligation in a rat infarction model [13,42]. Similarly, Hayashi et al reported that 6% of unfractionated bone marrow cells survived at 3 days in infarcted rat [13,42], and Freyman et al reported that ~5% of mesenchymal stem cells survived after transplanting into the infarcted porcine heart [43]. Clearly, there is considerable room for improvement, and solving the problem of cell death is central to successful remuscularization of the infarcted heart.…”
Section: Introductionmentioning
confidence: 99%